1997
DOI: 10.1007/s11664-997-0210-9
|View full text |Cite
|
Sign up to set email alerts
|

High performance SWIR HgCdTe detector arrays

Abstract: Short wave infrared (SWIR) devices have been fabricated using Rockwell's double layer planar heterostructure (DLPH) architecture with arsenic-ion implanted junctions. Molecular beam epitaxially grown HgCdTe/CdZnTe multilayer structures allowed the thin, tailored device geometries (typical active layer thickness was -3.5 Mm and cap layer thickness was -0.4 Mm) to be grown. A planar-mesa geometry that preserved the passivation advantages of the DLPH structure with enhanced optical collection improved the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…5,6 Recently, double layer planar heterojunction (DLPH) p-on-n photodiodes in molecular beam epitaxy (MBE) HgCdTe on CdZnTe substrates have been elaborated by As-ion implantation and the p-dopant activation by an open-tube Hg anneal. 7 The goal of this paper is comparing the ultimate-tonoise performance of InGaAs and HgCdTe photodiodes operated in the 1.5-3.7 µm spectral range. Results of theoretical predictions are compared with lems; excess thermal generation results in increased dark current and recombination which reduces photocurrent.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Recently, double layer planar heterojunction (DLPH) p-on-n photodiodes in molecular beam epitaxy (MBE) HgCdTe on CdZnTe substrates have been elaborated by As-ion implantation and the p-dopant activation by an open-tube Hg anneal. 7 The goal of this paper is comparing the ultimate-tonoise performance of InGaAs and HgCdTe photodiodes operated in the 1.5-3.7 µm spectral range. Results of theoretical predictions are compared with lems; excess thermal generation results in increased dark current and recombination which reduces photocurrent.…”
Section: Introductionmentioning
confidence: 99%
“…40 On the other hand, the reported SRH lifetime in In-doped, MBE grown n-type absorber layers is in the order of ~ 1 μs. [40][41][42][43] The direct experimental comparison of n-on-p and p-on-n photodetectors operating in the eSWIR band with cut-off wavelength of 2 μm has been undertaken by CEA-LETI in France on a vacancy doped p-type absorber (grown by LPE) and on In-doped n-type absorber (grown by MBE). The results show a similar quantum efficiency for both technologies.…”
Section: Theoretical Modelling Of Qe and Device Designmentioning
confidence: 99%
“…In addition, as shown in Figure 6, it can be observed that the internal QE strongly depends on the SRH lifetime of the minority carriers. While there is a significant lack of reported data on the minority carrier lifetime in absorber layers with composition suitable for operation in the eSWIR waveband, a recent report indicates minority electron lifetime in the 30-50 ns range for Hg-vacancy doped Hg0.62Cd0.38Te heteroepitaxially grown by MBE on Si substrates [12], whereas the SRH-limited minority hole lifetime in extrinsic n-type doped epilayers is typically of the order of 1 μs [12][13][14]. Based on preliminary results presented below, the electron minority carrier lifetime in Hg0.51Cd0.49Te grown by MBE on CdZnTe substrates is estimated to significantly exceed 50 ns.…”
Section: Theoretical Modelling Of Qe and Device Designmentioning
confidence: 99%